21st century children – do they still think like 20th century children?. (4th April 2011) - Collins, D; Doddamani, L
Abstract : Objective: To evaluate children's and parents' perceptions of hospital doctors' attire. Design: Questionnaire study asking children and parents to assign their thoughts and responses to photographs of a male or female doctor dressed formally and informally. Setting: Outpatient department, Children's Hospital, James Paget University Hospital NHS Trust, Great Yarmouth. 25 children were interviewed of which 8 were boys and 17 were girls. 24 parents were also interviewed using the same pictures. Main outcome measures: Children's and parents' preferences, with reference to the doctors dress. Results: Only 25% of children interviewed expressed anxiety about doctors wearing white coats. 79% of children rated male doctors as needing to be smart to be trustworthy. Women doctors were given more flexibility, with only 45% of children thinking they needed to be smartly dressed and many expressing a preference for more informal clothes. 75% of parents thought a white coat or clearly recognised uniform was a good idea with a strong preference for smart appearance. However, only 60% thought this applied in paediatricians, feeling doctors could dress more informally in this setting. Conclusions: Our children have not changed much. What we wear does matter as the majority of children consider formally dressed doctors as trustworthy but not friendly; and parents consider a recognisable uniform or white coat as important.